Prebiotic Potential of Gembili, Dahlia, and Yacon Tuber Flours - Tyastirin, Esti; Oktorina, Sarita; Febriyanti, Ikke Arina (State Islamic University of Sunan Ampel, 2024)
Inulin is a type of prebiotic which is generally produced from artichoke plants (Helianthus tuberosus). Considering the diversity of tubers in Indonesia, in this study the prebiotic potential of inulin was tested from various tubers, namely gembili tubers (Dioscororea esculenta), dahlia tubers (Dahlia Pinnata L.) and yakon tubers (Smallanthus sonchifolius). In this study, the prebiotic activity of tubers was tested against bifidiobacterium bacteria. Bacterial growth was carried out on MRS media, which is added with inulin from each tuber as much as 1% b/v gram. In addition to that negative control group and positive control group (comercial inulin) were added. During the incubation time of 24 hours, 48 and 92 hours, all varian group has positive correlation with the growth of Bifidiobacterium. The bigger correlation was found in Gembili tuber group with R = 0,9 and had the maxiumun bifidiobacterium colony which reached 14.4 x 108 CFU/ml.